[5.16] tongzhi shi MaLie zhuyi fazhan shi shang xinde weida lichengbei, shi ershi shiji liushi niandaide gongchandang xuanyan
'The 16 May Circular is a great new milestone in the history of the development of Marxism-Leninism, it is the Manifesto of the Communist Party of the 1960s'.